Study on DGPS signal reception transmitted from a reference station using trimble PRO-XR [compact disc] - 224595 Ami Hassan Md. Din (Skudai : Universiti Teknologi Malaysia, 2007)
Project Paper (Sarjana Muda Kejuruteraan (Geomatk) - Universiti Teknologi Malaysia, 2007